High-Performance flexible solid-state supercapacitor with an extended nanoregime interface through in situ polymer electrolyte generation - Anothumakkool, Bihag; Torris, Arun A. T.; Veeliyath, Sajna; Vijayakumar, Vidyanand; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
{Here, we report an efficient strategy by which a significantly enhanced electrodeelectrolyte interface in an electrode for supercapacitor application could be accomplished by allowing in situ polymer gel electrolyte generation inside the nanopores of the electrodes. This unique and highly efficient strategy could be conceived by judiciously maintaining ultraviolet-triggered polymerization of a monomer mixture in the presence of a high-surface-area porous carbon. The method is very simple and scalable, and a prototype, flexible solid-state supercapacitor could even be demonstrated in an encapsulation-free condition by using the commercial-grade electrodes (thickness = 150 mu m
Keywords: cyclic voltametry; impedance analysis; in situ polymer generation; interface; polymer electrolyte; supercapacitor

Unravelling the mechanism of electrochemical degradation of PANI in supercapacitors: achieving a feasible solution - Sekar, Pandiaraj; Anothumakkool, Bihag; Vijayakumar, Vidyanand; Lohgaonkar, Apurva; Kurungot, Sreekumar (Chemelectrochem, 2016)
Herein, we have investigated the mode of electrochemical degradation of polyaniline (PANI) when it was utilized as electrodes for supercapacitors. The PANI-based electrodes in supercapacitor devices were biased at a constant potential of 0.80 V, and the performance characteristics and property changes were carefully investigated as a function of the difference in the polarity of the electrodes. Subsequent to this, the analysis of the individual electrodes [positive (POS-PANI) and negative (NEG-PANI)] shows that the degradation mainly occurs at POS-PANI in comparison to NEG-PANI. Moreover, NEG-PANI retains a maximum capacitance of 510 Fg(-1), with a low charge-transfer resistance (R-CT) of 1.84 Omega and similar redox behavior in comparison to the fresh PANI (f-PANI). In contrast to this case, POS-PANI shows significant loss in capacitance (250 Fg(-1)) and increase in R-CT (3.5 Omega) with a disappearance of the characteristic redox behavior normally displayed by PANI. Furthermore, the drastic drop in the electrical conductivity for POS-PANI (1.2 Scm(-1)) compared to f-PANI (3.4 Scm(-1) and NEG-PANI (2.4 Scm(-1)) shows that the degradation of PANI occurs mainly at the anode (POS-PANI) and, thus, contributes to reduce the net performance of the cell. Hence, to ensure this potential-induced degradation of PANI in supercapacitors and also to promote the system stability, we made an asymmetric supercapacitor (ASC) by keeping PANI as a negative electrode and using carbon as a positive electrode. The derived system is found to display stable capacitance behavior before and after the potential application, in contrast to the ASC fabricated by using conventional method, that is, by keeping PANI as the positive electrode and carbon as the negative electrode. Furthermore, the durability analysis of the prototype solid-state ASC shows an enhanced durability of 27000 cycles with excellent columbic efficiency. The findings of the present study will be helpful in the development of highly stable supercapacitors and other similar energy systems when a material like PANI should be utilized for the electrode applications.
Keywords: asymmetric supercapacitors; cycle stability; electrochemical degradation; polarization; redox chemistry

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Rationally designed self-standing V2O5 electrode for high voltage non-aqueous all-solid-state symmetric (2.0 V) and asymmetric (2.8 V) supercapacitors - Ghosh, Meena; Vijayakumar, Vidyanand; Soni, Roby; Kurungot, Sreekumar (Nanoscale, 2018)
The maximum capacitive potential window of certain pseudocapacitive materials cannot be accessed in aqueous electrolytes owing to the low dissociation potential of 1.2 V possessed by water molecules. However, the inferior pseudocapacitance exhibited by the commonly used electrode materials when integrated with non-aqueous electrolytes still remains a challenge in the development of supercapacitors (SC). Proper selection of materials for the electrode and a rational design process are indeed important to overcome these practical intricacies so that such systems can perform well with non-aqueous electrolytes. We address this challenge by fabricating a prototype all-solid-state device designed with high-capacitive V2O5 as the electrode material along with a Li-ion conducting organic electrolyte. V2O5 is synthesized on a pre-treated carbon-fibre paper by adopting an electrochemical deposition technique that effects an improved contact resistance. A judicious electrode preparation strategy makes it possible to overcome the constraints of the low ionic and electrical conductivities imposed by the electrolyte and electrode material, respectively. The device, assembled in a symmetrical fashion, achieves a high specific capacitance of 406 F g(-1) (at 1 A g(-1)). The profitable aspect of using an organic electrolyte is also demonstrated with an asymmetric configuration by using activated carbon as the positive and V2O5 as the negative electrode materials, respectively. The asymmetric device displays a wide working-voltage window of 2.8 V and delivers a high energy density of 102.68 W h kg(-1) at a power density of 1.49 kW kg(-1). Moreover, the low equivalent series resistance of 9.9 Omega and negligible charge transfer resistance are observed in the impedance spectra, which is a key factor that accounts for such an exemplary performance.

Water-in-acid gel polymer electrolyte realized through a phosphoric acid-enriched polyelectrolyte matrix toward solid-state supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Torris, Arun A. T.; Chandran, Nikhil M. K.; Nair, Sanoop B.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2018)
A new concept of water-in-acid gel polymer electrolytes (GPEs) is introduced. The simple and scalable UV-light-assisted synthesis of a copolymer matrix possessing polyelectrolyte behavior, followed by swelling in minimally diluted H3PO4 (15.1 M/88 wt % aqueous solution), effects formation of a high proton-conducting, self-standing, and mechanically stable polyelectrolyte GPE (PGPE). Retention of high mechanical stability despite the presence of a large amount of liquid species makes it a promising candidate for replacing conventional GPEs. The high proton conductivity (9.8 X 10(-2) S cm(-1)) of the PGPE at an ambient temperature of 303 K is attributed to the high concentration of the conducting species present in the polymer matrix. The PGPE-based polyaniline (PANI) supercapacitor device (PANI-1) with a mass loading of 1 mg cm(-2) exhibits a high specific gravimetric capacitance of 385 F g(-1) at a current density of 0.25 mA cm(-2). At the same current density, the PANI-5 device retains high gravimetric and areal capacitance values of 258 F g(-1) and 1288 mF cm(-2), respectively. The low equivalent series resistance value of 0.78 Omega (for the PANI-5 device) further proves the excellent electrode-electrolyte interface formed by the water-in-acid GPE. A 100% capacitance retention even after 9000 continuous charge-discharge cycles strongly indicates the feasibility of adopting water-in-acid GPEs in future supercapacitors.

Dendrite growth suppression by Zn2+-integrated nafion ionomer membranes: beyond porous separators toward aqueous Zn/V2O5 batteries with extended cycle life - Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy Technology, 2019)
The dendritic/irregular growth of zinc deposits in the anode surface is often considered as a major intricacy limiting the lifespan of aqueous zinc-ion batteries. The effect of separators on the evolution of the surface morphology of the anode/cathode is never thoroughly studied. Herein, for the first time, the efficacy of the Zn2+-integrated Nafion ionomer membrane is demonstrated as a separator to effectively suppress the growth of irregular zinc deposits in the metallic anode of an aqueous Zn/V2O5 battery. The Zn2+-ions coordinated with the SO3- moieties in Nafion result in a high transference number of the Zn2+ cation, all the while facilitating a high ionic conductivity. The Zn2+-integrated Nafion membrane enables the Zn/V2O5 cell to deliver a high specific capacity of 510 mAh g(-1) at a current of 0.25 A g(-1), which is close to the theoretical capacity of anhydrous V2O5 (589 mAh g(-1)). Moreover, the same cell exhibits an excellent cycling stability of 88% retention of the initial capacity even after 1800 charge-discharge cycles, superior to that of the Zn/V2O5 cells comprising conventional porous separators.

Weak intermolecular interactions in covalent organic framework-carbon nanofiber based crystalline yet flexible devices - Mohammed, Abdul Khayum; Vijayakumar, Vidyanand; Halder, Arjun; Ghosh, Meena; Addicoat, Matthew; Bansode, Umesh; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2019)
<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">The redox-active and porous structural backbone of covalent organic frameworks (COFs) can facilitate high-performance electrochemical energy storage devices. However, the utilities of such 2D materials as supercapacitor electrodes in advanced self-charging power-pack systems have been obstructed due to the poor electrical conductivity and subsequent indigent performance. Herein, we report an effective strategy to enhance the electrical conductivity of COF thin sheets through the in situ solid-state inclusion of carbon nanofibers (CNF) into the COF precursor matrix. The obtained COF-CNF hybrids possess a significant intermolecular π···π interaction between COF and the graphene layers of the CNF. As a result, these COF-CNF hybrids (DqTp-CNF and DqDaTp-CNF) exhibit good electrical conductivity (0.25 × 10<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–3<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> S cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">), as well as high performance in electrochemical energy storage (DqTp-CNF: 464 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">). Also, the fabricated, mechanically strong quasi-solid-state supercapacitor (DqDaTp-CNF SC) delivered an ultrahigh device capacitance of 167 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> at 0.5 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">. Furthermore, we integrated a monolithic photovoltaic self-charging power pack by assembling DqDaTp-CNF SC with a perovskite solar cell. The fabricated self-charging power pack delivered excellent performance in the areal capacitance (42 mF cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">) at 0.25 mA cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; color: rgb(0, 0, 0); font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2<span style="color: rgb(0, 0, 0); font-family: Georgia, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);"> after photocharging for 300 s.

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.

Dioxolanone-anchored poly(allyl ether)-based cross-linked dual-salt polymer electrolytes for high-voltage lithium metal batteries - Vijayakumar, Vidyanand; Diddens, Diddo; Heuer, Andreas; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (ACS Applied Materials & Interfaces, 2020)
Novel cross-linked polymer electrolytes (XPEs) are synthesized by free-radical copolymerization induced by ultraviolet (UV)-light irradiation of a reactive solution, which is composed of a difunctional poly(ethylene glycol) diallyl ether oligomer (PEGDAE), a monofunctional reactive diluent 4-vinyl-1,3-dioxolan-2-one (VEC), and a stock solution containing lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in a carbonate-free nonvolatile plasticizer, poly(ethylene glycol) dimethyl ether (PEGDME). The resulting polymer matrix can be represented as a linear polyethylene chain functionalized with cyclic carbonate (dioxolanone) moieties and cross-linked by ethylene oxide units. A series of XPEs are prepared by varying the [O]/[Li] ratio (24 to 3) of the stock solution and thoroughly characterized using physicochemical (thermogravimetric analysis-mass spectrometry, differential scanning calorimetry, NMR, etc.) and electrochemical techniques. In addition, quantum chemical calculations are performed to elucidate the correlation between the electrochemical oxidation potential and the lithium ion-ethylene oxide coordination in the stock solution. Later, lithium bis(fluorosulfonyl)imide (LiFSI) salt is incorporated into the electrolyte system to produce a dual-salt XPE that exhibits improved electrochemical performance, a stable interface against lithium metal, and enhanced physical and chemical characteristics to be employed against high-voltage cathodes. The XPE membranes demonstrated excellent resistance against lithium dendrite growth even after reversibly plating and stripping lithium ions for more than 1000 h with a total capacity of 0.5 mAh cm(-2). Finally, the XPE films are assembled in a lab-scale lithium metal battery configuration by using carbon-coated LiFePO4 (LFP) or LiNi0.8Co0.15Al0.05O2 (NCA) as a cathode and galvanostatically cycled at 20, 40, and 60 degrees C. Remarkably, at 20 degrees C, the NCA-based lithium metal cells displayed excellent cycling stability and good capacity retention (>50%) even after 1000 cycles.
Keywords: cross-linked polymer electrolyte; dual-salt electrolyte; high-voltage cathode; lithium metal battery; solvent-free photopolymerization

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Nafion lonomer-based single component electrolytes for aqueous Zn/MnO2 batteries with long cycle life - Ghosh, Meena; Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2020)
Recently, aqueous rechargeable Zn/MnO2 batteries are emerging as promising energy storage aids owing to their improved safety, low cost of fabrication, and high energy density. However, the rapid decay of capacity during extended charge- discharge cycles hinders the prospect of this technology beyond lab-scale. In the conventional Zn/MnO2 cell, additives such as Mn2+ have been used to tackle the stability issue. Here, we demonstrate that cycling performance of the Zn/MnO2 cell can be improved substantially by using Nafion ionomer as the separator in combination with zinc-ion conducting electrolytes. The Nafion ionomer-based Zn/MnO2 cells do not require any Mn' additive in the electrolyte and hence termed as ``single component'' electrolytes. The postmortem study of the post-cycled electrodes reveals that the structural evolution of both the anode and cathode in various electrolytes (1 M Zn(CF3SO3)(2), 1 M ZnSO4 center dot 7H(2)O, and 3 M ZnSO4 center dot 7H(2)O) during prolonged cycling significantly influences the cycle life of the respective cells. Optimizing the Nafion ionomer membrane with a suitable electrolyte could render the desired combination of high capacity and high cycle life for a Zn/MnO2 cell.
Keywords: aqueous Zn-ion batteries; Cycling stability; dendrite suppression; Electrodeposition; MnO2; Nafion ionomer separator; single component electrolyte

Scalable synthesis of manganese-doped hydrated vanadium oxide as a cathode material for aqueous zinc-metal battery - Ghosh, Meena; Dilwale, Swati; Vijayakumar, Vidyanand; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2020)
Rechargeable aqueous zinc-metal batteries (ZMBs) are considered as potential energy storage devices for stationary applications. Despite the significant developments in recent years, the performance of ZMBs is still limited due to the lack of advanced cathode materials delivering high capacity and long cycle life. In this work, we report a low-temperature and scalable synthesis method following a surfactant-assisted route for preparing manganese-doped hydrated vanadium oxide (MnHVO-30) and its application as the cathode material for ZMB. The as-prepared material possesses a porous architecture and expanded interlayer spacing. Therefore, the MnHVO-30 cathode offers fast and reversible insertion of Zn2+ ions during the charge/discharge process and delivers 341 mAh g(-1) capacity at 0.1 A g(-1). Moreover, the MnHVO-30 parallel to Zn cell retains 82% of its initial capacity over 1200 stability cycles, which is higher compared to that of the undoped system. Besides, a quasi-solid-state home-made pouch cell with an area of 3.3 x 1.6 cm(2) and 3.6 mg cm(-2) loading is assembled, achieving 115 mAh g(-1) capacity over 100 stability cycles. Therefore, this work provides an easy and attractive way for preparing efficient cathode materials for aqueous ZMBs.
Keywords: anionic surfactant; hydrated vanadium pentoxide; Nafion ionomer membrane; post-lithium battery; quasi-solid-state battery

In situ polymerization process: an essential design tool for lithium polymer batteries dagger - Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (Energy & Environmental Science, 2021)
Polymer electrolytes (PEs), a type of solid-state electrolytes (SSEs), have been in contention for nearly half a century to replace organic liquid electrolytes (LEs) that are used in state-of-the-art lithium-ion batteries (LIBs). They are envisaged to accelerate the industrial-scale production of safe, energy-dense, flexible, and thin lithium polymer batteries (LPBs). LPBs are expected to be widely employed for electric propulsion and other futuristic applications, such as flexible electronics and the Internet of Things (IoT). Even though several polymer architectures and chemistries have been attempted so far, PEs that can outperform LEs remain a real challenge. Apart from inadequate Li+-ion transport properties, challenges concerning the integration of PEs and the engineering of compatible, robust, and durable interfaces and interphases at both the electrodes of LPBs must be appropriately addressed. Recently, the in situ polymerization process has been widely employed as a robust fabrication tool for surpassing the intricacies related to the integration of PEs in LPBs. Hence, in this review, we focus on the in situ polymerization processes that employ various polymerization methods (e.g., free-radical polymerization, ionic polymerization, electropolymerization, condensation polymerization, etc.), functional monomers and oligomers (e.g., acrylate, methacrylate, allyl and vinyl ethers, epoxides, etc.), and PE integration strategies for the fabrication of lithium (ion and metal) polymer batteries (LIPBs and LMPBs). Additionally, this review also evaluates the approaches that have been developed until now to implement the in situ processing of LPBs from large-sized pouch cells to flexible-/printable-batteries and even microbatteries.

In situ preparation of ionomer as a tool for triple-phase boundary enhancement in 3D graphene supported Pt catalyst - Gangadharan, Pranav K.; Vijayakumar, Vidyanand; Nediyirakkal, Shijil A.; Fernandez, Roshni Tresa; Siddharthan, V. Adhrika; Kurungot, Sreekumar (Advanced Sustainable Systems, 2021)
For improving the performance of platinum electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs), it is important to enhance the Pt utilization level in the catalyst systems. A high performing electrocatalyst (Pt/3DNG) is developed for PEMFC applications by using nitrogen-doped 3D graphene (3DNG) as the support material and an in situ grafted active ``triple-phase boundary'' to more precisely control the formation of the proton conducting ionomer interface at the active sites. Considering the 3D morphology of the system, during the electrode fabrication for realistic single-cell evaluation, the concept of in situ generation of the proton conducting-ionomer based ``active triple-phase boundary'' is introduced, which could potentially replace the conventional method of using Nafion ionomer for the electrode preparation. The monomers owing to their small-size can access the pores and inner regions of the 3DNG support, which on UV-curing, undergo polymerization and transform into an ionomer with an extended interfacial network into the nanoregimes of 3DNG. Single cell evaluation of the membrane electrode assembly in a high-temperature PEMFC by using phosphoric acid doped polybenzimidazole membrane demonstrates the utility of the present strategy.
Keywords: electrocatalysts; fuel cells; graphene; oxygen reduction reaction

Interconnected polyaniline nanostructures: enhanced interface for better supercapacitance retention - Mooss, Vandana A.; Vijayakumar, Vidyanand; Kurungot, Sreekumar; Athawale, Anjali A. (Polymer, 2021)
Polyaniline and its nanocomposites have emerged as desirable electrode materials for supercapacitors. However, achieving specific capacitance with long-term cyclic stability is still a challenge. The present study reports on novel hierarchically porous and cross-linked polyaniline synthesized by a method employing aniline (monomer) and phytic acid (dopant acid) in the presence of octyltrimethyl ammonium bromide (OTAB) surfactant. The electrochemical performance of the phytic acid doped sample has been compared with HCl doped samples, the former being superior, i.e., a specific capacitance of 523 and 325 F g(-1) at current densities of 0.25 and 10 A g(-1), respectively. Additionally, the same possess excellent cycling stability with retention of similar to 88% of its initial capacitance over 10,000 charge-discharge cycles. Further, the phytic acid doped sample exhibited a lower equivalent series resistance (0.98 Omega cm(2)) than the HCl doped sample (1.26 Omega cm(2)). These results reveal the capability of the phytic acid doped hierarchical polyaniline sample as a promising active material for electrochemical applications.
Keywords: Cyclic stability; Hierarchical polyaniline; Supercapacitance retention

Naphthalene dianhydride organic anode for a `rocking-chair' zinc-proton hybrid ion battery - Ghosh, Meena; Vijayakumar, Vidyanand; Kurian, Maria; Dilwale, Swati; Kurungot, Sreekumar (Dalton Transactions, 2021)
Rechargeable batteries consisting of a Zn metal anode and a suitable cathode coupled with a Zn2+ ion-conducting electrolyte are recently emerging as promising energy storage devices for stationary applications. However, the formation of high surface area Zn (HSAZ) architectures on the metallic Zn anode deteriorates their performance upon prolonged cycling. In this work, we demonstrate the application of 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTCDA), an organic compound, as a replacement for the Zn-metal anode enabling the design of a `rocking-chair' zinc-proton hybrid ion battery. The NTCDA electrode material displays a multi-plateau redox behaviour, delivering a specific discharge capacity of 143 mA h g(-1) in the potential window of 1.4 V to 0.3 V vs. Zn|Zn2+. The detailed electrochemical characterization of NTCDA in various electrolytes (an aqueous solution of 1 M ZnOTF, an aqueous solution of 0.01 M H2SO4, and an organic electrolyte of 0.5 M ZnOTF/acetonitrile) reveals that the redox processes leading to charge storage involve a contribution from both H+ and Zn2+. The performance of NTCDA as an anode is further demonstrated by pairing it with a MnO2 cathode, and the resulting MnO2||NTCDA full-cell (zinc-proton hybrid ion battery) delivers a specific discharge capacity of 41 mA h g(total)(-1) (normalized with the total mass-loading of both anode and cathode active materials) with an average operating voltage of 0.80 V.

Sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2||Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.

Electrodeposited layered sodium vanadyl phosphate (NaxVOPO4 center dot nH(2)O) as cathode material for aqueous rechargeable zinc metal batteries - Dilwale, Swati; Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy & Fuels, 2022)
Aqueous rechargeable zinc metal batteries (ARZMBs) present a safer and cost-effective solution for energy storage in stationary applications. However, a major challenge is the lack of suitable cathode materials simultaneously exhibiting high operating voltage and long cycling stability. Herein, we report the polyanionic sodium-intercalated layered vanadyl phosphate [NaxVOPO4 center dot nH(2)O (NVP)] as a suitable high-voltage and stable cathode for ARZMBs. This work employs a simpler electrochemical route (electrodeposition) for the synthesis of NVP over functionalized carbon fiber substrates and its application as a binder-free cathode in ARZMBs. The electrodeposited NVP possesses a morphology of vertically aligned well-separated nanosheet bundles resembling a flower. When used as the ARZMB cathode, the NVP electrode delivers a specific discharge capacity of 100 mA h g(-1) at 0.033 A g(-1) and high cycling stability (98% retention of the initial capacity over 1100 cycles at 0.333 A g(-1)) in a mild aqueous electrolyte with moderate zinc salt concentration. The observed electrochemical performance of NVP is credited to the synergistic effect of unique nanoflower morphology, the pillaring effect offered by the intercalated Na, and the intimate contact of the active material with the carbon fiber network. These factors are favorable for enhancing the transport of the electrolyte ions and electrons and maintaining the structural stability of the electrode during long-term cycling. The NVP electrode could also deliver appreciable performance (a discharge capacity of 73 mA h g(-) 1 and a current density of 0.033 A g(-1)) in quasi-solidstate ARZMB cells employing PVA/Zn(CF3SO3)(2) gel electrolyte.

Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries

2D layered nanomaterials as fillers in polymer composite electrolytes for lithium batteries - Vijayakumar, Vidyanand; Ghosh, Meena; Asokan, Kiran; Sukumaran, Santhosh Babu; Kurungot, Sreekumar; Mindemark, Jonas; Brandell, Daniel; Winter, Martin; Nair, Jijeesh Ravi (Advanced Energy Materials, 2023)
Polymer composite electrolytes (PCEs), i.e., materials combining the disciplines of polymer chemistry, inorganic chemistry, and electrochemistry, have received tremendous attention within academia and industry for lithium-based battery applications. While PCEs often comprise 3D micro- or nanoparticles, this review thoroughly summarizes the prospects of 2D layered inorganic, organic, and hybrid nanomaterials as active (ion conductive) or passive (nonion conductive) fillers in PCEs. The synthetic inorganic nanofillers covered here include graphene oxide, boron nitride, transition metal chalcogenides, phosphorene, and MXenes. Furthermore, the use of naturally occurring 2D layered clay minerals, such as layered double hydroxides and silicates, in PCEs is also thoroughly detailed considering their impact on battery cell performance. Despite the dominance of 2D layered inorganic materials, their organic and hybrid counterparts, such as 2D covalent organic frameworks and 2D metal-organic frameworks are also identified as tuneable nanofillers for use in PCE. Hence, this review gives an overview of the plethora of options available for the selective development of both the 2D layered nanofillers and resulting PCEs, which can revolutionize the field of polymer-based solid-state electrolytes and their implementation in lithium and post-lithium batteries.
Keywords: 2D materials; clay minerals; covalent organic frameworks; metal-organic frameworks; MXene; polymer composite electrolyte; solid-state batteries

Electrode|electrolyte interface enhancement in quasi-solid-state zinc-air batteries through an anion conducting polymer electrolyte interlayer by in situ polymerization - Kurian, Maria; Vijayakumar, Vidyanand; Manna, Narugopal; Kanheerampockil, Fayis; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2023)
This work introduces a novel concept of electrode|electrolyte interface enhancement using an ultraviolet (UV) light-assisted in situ polymerization strategy to improve the performance of quasi-solid-state zinc-air batteries (ZABs). The suitability of the UV polymerization strategy to process a mechanically stable OH- conducting anion exchange polymer electrolyte membrane (AEPEM) reinforced by a glass fiber (GF) separator is also reported. The in situ polymerized ionomer-skin/interlayer (a thin anion-conducting polymer coating over the air-cathode of ZAB) acts as a buffer layer to narrow down the performance gap generally observed between ZABs possessing quasi-solid-state electrolytes and standard liquid electrolytes, respectively. For instance, when combined with the in situ polymerization strategy, a rechargeable ZAB (rZAB) based on an AEPEM-GF composite membrane delivered a high power density of 140 mW cm(-2), higher than that of the one without an in situ polymerized ionomer interlayer (120 mW cm(-2)). Notably, in a flexible rZAB configuration, this new strategy resulted in enhanced rate capability and cycling stability for 14 h at an operating current density of 2 mA cm(-2).

F-doped nickel cobalt oxide-carbon composite electrocatalysts paired with mechanically robust anion-conducting chitosan membranes for flexible and rechargeable zinc-air batteries - Kurian, Maria; Ranganath, Suresha P.; Vijayakumar, Vidyanand; Sivadasan, Sneha; Kurian, Rachna Maria; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Energy Materials, 2024)
High-performing, cost-effective electrocatalysts and anion-conducting polymer electrolyte membranes are essential for realizing commercially affordable zinc-air batteries (ZABs). In this context, the present work deals with the development of a bifunctional electrocatalyst and an anion-exchange quasi-solid-state electrolyte membrane (based on quaternary ammonium group-grafted chitosan) for demonstrating flexible and rechargeable ZABs. The electrocatalyst composed of NiCoO2 nanoparticles supported on a carbon framework showcased substantial advancements in its ability to catalyze both oxygen reduction and evolution reactions (ORR and OER) due to the heteroatom doping by fluorine. For instance, the optimized electrocatalyst (F-NCO-ADC-600) exhibited an onset potential of 0.96 V vs RHE with a half-wave potential of 0.83 V vs RHE for ORR, a comparable performance with the state-of-the-art Pt/C (1.0 and 0.86 V vs RHE, respectively). On a similar note, the same catalyst also displayed an overpotential of 340 mV vs RHE for OER at a current density of 20 mA cm(-2), close to that of a standard RuO2 catalyst (337 mV vs RHE). In the context of polymer electrolytes, the quaternary ammonium-group-grafted chitosan membrane depicted superior ionic conductivity, liquid electrolyte uptake, and mechanical properties, thereby proving to be an efficient anion-conducting polymer electrolyte membrane. The realistic application of the developed electrocatalyst and the polymer electrolyte membrane is demonstrated in the ZAB prototypes. The assembled rechargeable ZAB (RZAB) delivered a power density of 207 mW cm(-2) and maintained high-rate capability and cycling stability, notably in a flexible configuration (f-RZABs). Thus, this work provides a strategy for the rational design of anion-exchange membranes and bifunctional electrocatalysts for f-RZABs.
Keywords: anion-conducting polymer electrolytemembrane; F-doping; flexible and rechargeable zinc-air batteries(f-RZABs); oxygen evolution reaction(OER); oxygen reduction reaction (ORR)